Preparation of Powdered Infant Formula: Could Product's Safety Be Improved?. Issue 4 (October 2018) - Losio, Marina Nadia; Pavoni, Enrico; Finazzi, Guido; Agostoni, Carlo; Daminelli, Paolo; Dalzini, Elena; Varisco, Giorgio; Cinotti, Stefano
Abstract : ABSTRACT: The recent outbreak of Salmonella Agona linked to the consumption of infant formula (powdered formula) has rekindled the attention about the correct procedures for preparation and use of these products. International guidelines have already been published so far, particularly in association with Cronobacter sakazakii in early 2000s. FAO/WHO suggested to reconstitute formula with water at no less than 70°C. We therefore contaminated powdered formula with low levels of Salmonella spp and C sakazakii to evaluate the pathogens inactivation during the formula preparation using water at 70°C. In these conditions we observed a survival of both pathogens, indicating that the suggested recommendations may be not enough to guarantee the safety of this product. Higher temperatures are needed to reduce the biological risk, even if it may be not easily realized in actual domestic conditions. Moreover, the impact on the nutritional value of reconstituted formulas should be evaluated.